2017
DOI: 10.1080/08827508.2017.1415205
|View full text |Cite
|
Sign up to set email alerts
|

Mill scale as a potential additive to improve the quality of hematite ore pellet

Abstract: Hematite pellet is required to be indurated at very high temperature to achieve its good strength as there is no exothermic heat of oxidation unlike magnetite. As mill scale contains mainly FeO and Fe 3 O 4 , any minor amount of its addition in pellet can provide in situ heat and enhance diffusion bonding and sintering. In this study, the mill scale generated in steel plant is added as magnetite input in hematite pellet both in acidic and in basic condition. It has been found that in fluxed pellet, mill scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…While this poor densification can be attributed to the low temperature and thus low diffusion rate, in the past, cold sintering of other oxides has achieved higher relative densities with the temperatures lower than 130‐250°C: >90% (~100°C, 77‐387 MPa) for ZnO, and 77.5‐84.5% (30°C, 200‐500 MPa) for HBO 2 ‐II . Yet, our work uniquely provides decent densification (55.8‐64.2%) with lower temperature (~130‐250°C) when compared with previous sintering work of iron oxides: 55% (400‐500°C, 200 MPa, maghemite nanoparticles), and ~76% (1250°C, hematite pellets) . To improve densification, in the future, multiple steps or reactive transient liquid phases can be introduced to the sintering process, followed by postsintering treatments …”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…While this poor densification can be attributed to the low temperature and thus low diffusion rate, in the past, cold sintering of other oxides has achieved higher relative densities with the temperatures lower than 130‐250°C: >90% (~100°C, 77‐387 MPa) for ZnO, and 77.5‐84.5% (30°C, 200‐500 MPa) for HBO 2 ‐II . Yet, our work uniquely provides decent densification (55.8‐64.2%) with lower temperature (~130‐250°C) when compared with previous sintering work of iron oxides: 55% (400‐500°C, 200 MPa, maghemite nanoparticles), and ~76% (1250°C, hematite pellets) . To improve densification, in the future, multiple steps or reactive transient liquid phases can be introduced to the sintering process, followed by postsintering treatments …”
Section: Discussionmentioning
confidence: 93%
“…41 Yet, our work uniquely provides decent densification (55.8-64.2%) with lower temperature (~130-250°C) when compared with previous sintering work of iron oxides: 55% (400-500°C, 200 MPa, maghemite nanoparticles), 12 and ~76% (1250°C, hematite pellets). 13 To improve densification, in the future, multiple steps 42,43 or reactive transient liquid phases 30,44,45 can be introduced to the sintering process, followed by postsintering treatments. 46…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flux free acidic hematite ore pellets have very high induration temperature because of absence of any oxidation reaction and limited amount of diffusion bonding at lower temperature [16]. Figure 4 [18] shows minimum RDI at 0.3 basicity and beyond that, both RDI and CCS increase and reducibility decreases with the increase in basicity. However, a very good CCS is observed at 0.3 basicity as well.…”
Section: Properties Of Iron Ore Pelletsmentioning
confidence: 99%
“…The addition of mill scale can reduce induration temperature and increase CCS of acidic hematite ore pellets. In a separate study [18], the effect of mill scale in hematite ore on pellet properties was studied. It was found that the use of 15 % mill scale in acidic pellet can reduce the induration temperature up to 1250 °C and improve pellet properties viz CCS, RI, RDI, and swelling index.…”
Section: Properties Of Iron Ore Pelletsmentioning
confidence: 99%